2020
DOI: 10.1111/jcmm.15430
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Akt and NF‐κB pathway mediates inhibitory effect of gas6 on monocytes‐endothelial cells interactions stimulated by P. gingivalis‐LPS

Abstract: Correlation between periodontitis and atherosclerosis is well established, and the inherent mechanisms responsible for this relationship remain unclear. The biological function of growth arrest‐specific 6 (gas6) has been discovered in both atherosclerosis and inflammation. Inhibitory effects of gas6 on the expression of inflammatory factors in human umbilical vein endothelial cells (HUVECs) stimulated by Porphyromonas gingivalis lipopolysaccharide ( P. gingivalis ‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 50 publications
(85 reference statements)
1
23
0
Order By: Relevance
“…Here, GAS6-AS2 expression was found to be abnormally up-regulated in HK2 cells treated with LPS and renal tissues from sepsis AKI rats, which was consistent with previous results. Additionally, GAS6-AS2 is associated with the apoptosis of melanoma cells [ 14 ], hepatocellular carcinoma cells [ 10 ], and osteosarcoma cells [ 12 ], as well as inflammation [ 15 ]. We found that down-regulation of GAS6-AS2 could significantly relieve apoptosis, inflammatory response, and oxidative stress in renal epithelial cells, as well as reduce kidney pathology in AKI rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, GAS6-AS2 expression was found to be abnormally up-regulated in HK2 cells treated with LPS and renal tissues from sepsis AKI rats, which was consistent with previous results. Additionally, GAS6-AS2 is associated with the apoptosis of melanoma cells [ 14 ], hepatocellular carcinoma cells [ 10 ], and osteosarcoma cells [ 12 ], as well as inflammation [ 15 ]. We found that down-regulation of GAS6-AS2 could significantly relieve apoptosis, inflammatory response, and oxidative stress in renal epithelial cells, as well as reduce kidney pathology in AKI rats.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA GAS6-AS2 has been shown to act as an oncogene to promote the development of a number of tumors, such as hepatocellular carcinoma [ 10 ], breast cancer [ 11 ], osteosarcoma [ 12 ], non-small-cell lung cancer [ 9 ], bladder cancer [ 13 ], and melanoma [ 14 ]. In addition, existing results indicated that GAS6-AS2 was related to inflammatory response [ 15 ] and apoptosis [ 14 ], which are also the important features of septic AKI. However, the role and mechanism of GAS6-AS2 in sepsis-related AKI are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We observed a strong increase in levels of p65 in the nuclei of microglia exposed to LPS, which was markedly reduced when cells were co-incubated with Gas6. Gas6 has previously been shown to attenuate neuroinflammation through inhibition of the NF-κB family in damaged brain tissue [ 52 ] and both the Mer and Axl receptors have been shown to be involved in the Gas6-mediated response [ 53 ]. Here, we have expanded the known associations by demonstrating that Gas6 alters GM-CSF signalling through modification of the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…AXL originates from hematopoietic, epithelial, and mesenchymal cells and is expressed in most human cells [ 7 ], whereas GAS6 is widely expressed in a variety of tissues such as the bone, lung, heart, and kidney, but its expression level is low in the liver [ 37 ]. P. gingivalis LPS inhibits the expression of AXL and GAS6 in human umbilical vein endothelial cells [ 38 ]. The inhibitory effect of Escherichia coli LPS on the expression of AXL in human umbilical vein endothelial cells has also been reported [ 39 ].…”
Section: Discussionmentioning
confidence: 99%